2007
DOI: 10.1038/nmat2081
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity hydrogen storage in lithium and sodium amidoboranes

Abstract: The safe and efficient storage of hydrogen is widely recognized as one of the key technological challenges in the transition towards a hydrogen-based energy economy. Whereas hydrogen for transportation applications is currently stored using cryogenics or high pressure, there is substantial research and development activity in the use of novel condensed-phase hydride materials. However, the multiple-target criteria accepted as necessary for the successful implementation of such stores have not yet been met by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
366
2
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 589 publications
(381 citation statements)
references
References 24 publications
11
366
2
2
Order By: Relevance
“…The Na-N distances in the range of 2.414-2.545 Å are close to the Na-N distance (2.35 Å) in NaNH 2 BH 3 . 13 Such cationic chains are then surrounded by BH 4 À anions with Na and B distances in a range of 2.97 to 3.05 Å. For Mg(BH 4 ) 2 -NH 2 NH 2 complex a new phase with Mg(BH 4 ) 2 /NH 2 NH 2 = 1/3 was identified, which can be indexed using a trigonal P% 31c cell with lattice parameters of a = 13.8385 Å, c = 7.8284 Å, and V = 1298.32 Å 3 .…”
Section: +mentioning
confidence: 99%
“…The Na-N distances in the range of 2.414-2.545 Å are close to the Na-N distance (2.35 Å) in NaNH 2 BH 3 . 13 Such cationic chains are then surrounded by BH 4 À anions with Na and B distances in a range of 2.97 to 3.05 Å. For Mg(BH 4 ) 2 -NH 2 NH 2 complex a new phase with Mg(BH 4 ) 2 /NH 2 NH 2 = 1/3 was identified, which can be indexed using a trigonal P% 31c cell with lattice parameters of a = 13.8385 Å, c = 7.8284 Å, and V = 1298.32 Å 3 .…”
Section: +mentioning
confidence: 99%
“…The interaction between ammonia borane and LiH leads to the formation of LiNH 2 BH 3 with substantially different dehydrogenation behavior. [97,98] Maintaining high-weight-percent hydrogen storage, whilst reducing T dec and enhancing reversibility, will represent a major milestone and a potential "show-stopper" for the transition to a hydrogen economy. However, much more fundamental research is required to understand the physical and chemical Figure 13.…”
Section: Hydrogen Storage Materialsmentioning
confidence: 99%
“…1) In contrast to the compressed hydrogen and the liquefaction hydrogen, hydrogen storage in the solid state is the most promising alternative. [2][3][4][5] In the past decades, the complex hydrides consisting of light elements, e.g., alanates, [6][7][8][9][10] amides, [11][12][13][14][15] borohydrides [16][17][18][19][20] and ammonia borane (AB), [21][22][23] have been attracting extensive attention as the potential hydrogen storage materials due to their high gravimetric and volumetric hydrogen storage densities. In particular, significant efforts have been made in recent years with metal amide-hydride combined systems since Chen et al reported that lithium nitride, Li 3 N could absorb/desorb reversibly 11.4 mass% of hydrogen in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…12) Recently, a dramatically improved dehydrogenation performance was obtained through substituting one or two H atoms in the NH 3 group of ammonia borane (AB) by alkali or alkaline-earth metals. 22,29) Xiong et al reported that $ 10:9 mass% hydrogen was librated from LiNH 2 BH 3 obtained by ball milling the mixture of NH 3 BH 3 and LiH at significantly lower temperatures with respect to NH 3 BH 3 itself. 22) More interestingly, the reaction between NH 3 BH 3 and LiH in THF delivers more than 14 mass% of hydrogen at a temperature as low as 40 C. 30) Significantly, combining compounds containing NH x group with metal hydrides results in interesting hydrogen storage systems with improved thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%